Racial inequalities in mortality from violent causes in Brazil (Research, Society and Development, 2022)
The deaths by external causes or violence were in first place since the end of 1980, specially in big urban centers. The importance of this causes change in one of most serious public health problems in majority countries in the world. These kind of death were correlated to social and economic disparities among regions, countries and population, rich and poor and etnic/social groups. These social inequalities were been showed by many autors. In Brazil, there are limited comprehension about race/skin color, urbanicity and metropolitan region like determinants for social population composition and premature deaths. The risk to die by homicide is twice higher for black people than for white ones. Among brasilian black people this cause of death exceeded Colombian registers, considered one of the most violents countries in the world because civil war and drug trafficking.